Contemporary Islamic educational discourse and the philosophy of empowerment - Rahath House, Yousef; Hashim, Rosnani (Association of Muslim Social Scientists, 2013)
The central concern of this article is to examine the contemporary Islamic educational discourse from the perspective of the philosophy of empowerment. In line with this view, it proposes a new conceptual framework for empowerment in lieu of the traditional views, which consider empowerment in terms of infrastructural developments or shifting power from the powerful to the powerless. We suggest that empowerment should be viewed as a social process that helps people gain control over their lives by enabling them to act on issues important to them. Considered in this light,education that seeks to empower people must be a process that provides the fundamental freedom and resources to understand the world and grants the ability to change that world. Contemporary Islamic educational discourses are evaluated on this basis to determine to what extent Islamic educators are engaged with the idea of empowerment proposed in this article.